2005
DOI: 10.1103/physreve.72.056102
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field limit of systems with multiplicative noise

Abstract: A detailed study of the mean-field solution of Langevin equations with multiplicative noise is presented. Three different regimes depending on noise-intensity (weak, intermediate, and strongnoise) are identified by performing a self-consistent calculation on a fully connected lattice. The most interesting, strong-noise, regime is shown to be intrinsically unstable with respect to the inclusion of fluctuations, as a Ginzburg criterion shows. On the other hand, the self-consistent approach is shown to be valid o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
7
39
0
Order By: Relevance
“…All moments m k starting from 2D/σ 2 + 1 scale with the same exponent, while the usual scaling m k ∼ m k obtains for k ≤ 2D/σ 2 + 1. This same behavior was observed in a mean-field study of nonequilibrium, MN1 complete wetting as reported in [14], and seems to be a common feature of multiplicative-noise controlled transitions.…”
Section: If P > 2d/σsupporting
confidence: 85%
See 1 more Smart Citation
“…All moments m k starting from 2D/σ 2 + 1 scale with the same exponent, while the usual scaling m k ∼ m k obtains for k ≤ 2D/σ 2 + 1. This same behavior was observed in a mean-field study of nonequilibrium, MN1 complete wetting as reported in [14], and seems to be a common feature of multiplicative-noise controlled transitions.…”
Section: If P > 2d/σsupporting
confidence: 85%
“…This represents a strong form of multiscaling, very similar to the one reported for the moments in the self-consistent solution for MN1 [14].…”
Section: A the Case Mn1supporting
confidence: 79%
“…In particular, in these systems the random variations of temperature, food resources, and other environmental parameters can be described using models in which multiplicative noise sources are present [8,16,17]. In fact, the models that can effectively describe experimental data in population dynamics are those with multiplicative noise, which can give rise to behavior characterized by a power law [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In population dynamics, random fluctuations are always modeled as a multiplicative noise source, because the dynamics of the population density is driven by statedependent fluctuation amplitude, 4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] which allows to reproduce experimental data. This means that, the effects of fluctuations have to be proportional to the activity density, which is the predator density in our system.…”
Section: Dynamics Of the Predator Populationmentioning
confidence: 99%